The effect of football practice duration on improving the balancing skills of football players with hearing impairments - Sobyanin, F. I.; Zavalishina, S.Y.; Kachenkova, E. S.; Bobkova, S. N. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The present study is aimed at determining the possibilities of maintaining balance in people with hearing impairments who practice in the specialized football section.